PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA PELAYARAN - Pujiati Pujiati (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
This research aims to analyze the corporate criminal liability and criminal system toward the corporation that carry out the shipping criminal action based on Law No. 17 Year 2008 about Shipping. The type of this research is a normative juridical research with the consideration that this research departs from the analysis of the legislation. The methods used are legislation approach, conceptual approach and case approach. Legal materials collection techniques with the study of literature. Legal materials obtained were processed by analyzing use of reasoning logically and systematically with an interpretation of systematic, grammatical, telelogis and futuristic interpretation then be concluded by deductive.Based on the result of research concluded that corporate criminal liability and corporate criminal system toward shipping criminal action under Law No. 17 Year 2008 about Shipping in its implementation still many weakness, among others: when the corporation to be the actor; how corporation can be responsible; what types of sanctions that can be imposed for corporation; unregulated substitutes criminal fines are not paid by the corporation; unregulated the implementation guidelines on corporate criminal; unregulated separation between the offense and the crime; unregulated the terms of countermeasures the shipping criminal action. Based on the description, Law No. 17 Year 2008  about shipping for the future have to see the weaknesses mentioned above and should be amended. Keywords : Corporate Criminal Liability, Shipping Criminal Action